Gas gain measurement for charged particle spectroscopy using glass GEM in low-pressure P-10 gas. (1st January 2023) - Unno, Y.; Fujiwara, T.; Kishimoto, Y.; Sanami, T.
Abstract: A glass gas electron multiplier (GEM) was tested to evaluate performance for charged particle spectroscopy in a gas chamber. The test was done with varying low-pressure Ar/CH4 mixture gas (9:1, P-10) for evaluation of effective electron multiplication gain (gas gain) with the relationship between supplied voltage to GEM (GEM ΔV), energy and timing resolution of signals. The GEM ΔV is parameterized as a function of gas gain and pressure from experimental results. The signal-to-noise ratio on the anode signal was significantly improved due to electron multiplication by the glass GEM in comparison with traditional grid gas ionization chamber. A test using Ar/CO2 mixture gas (9:1) shows that GEM ΔV is successfully reduced with keeping gas gain and energy resolution comparable. Time difference between anode and cathode signals behaves reasonably with drift time of initial electrons. We conclude that charged particle spectrometer using glass GEM can be designed by using obtained parameter. The spectrometer is useful especially for low energy charged particle due to the gas gain.